Estudio del movimiento de estructuras dinámicas mediante el uso de GPS (ING) - G. Serpas, Juan; Ramírez, Manuel; Colomer, Ricardo (Uniciencia, 2004)
The School of Topography, Cadastre and Geodesy of the Universidad Nacional, researched the use of the global positioning system (GPS) for the determination of movements on civil structures. These structures are designed in such a way to have a degree of elasticity to avoid possible fractures. The research activity was aimed at the development and analysis of procedure and methodologies to determine in an efficient, simple, and economic way the determination of the movement of civil structures in different periods. Spectral techniques were applied to the data provided by a GPS receiver placed on the Tempisque river bridge. The magnitude of the movements of the bridge are investigated for long and short periods.